DETERMINAN YANG MEMPENGARUHI TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH DI INDONESIA - Alvin Yoga Fanany, (2021)
This research aims to examine the level of mandatory disclosure in local government financial reports with the determinants that affect the number of members of the legislative body, debt, population, level of welfare, and age of the local government as control variables. The population in this study were all regional government financial reports in Indonesia. The sampling consisted of 248 local governments in Indonesia based on the purposive sampling method with the criteria for financial statements that have been audited by the Supreme Audit Agency in 2018. Hypothesis testing in this study uses Multiple Regression Analysis with the SPSS Version 25 program. These results indicate that the number of members of the legislative body, debt, and the total population has no effect on the level of disclosure of local government financial statements (LKPD) and the level of welfare has an effect on the level of disclosure of LKPD.